Holistic Islamic Education Curriculum Towards Society 5.0 - Putri Adona; Zainur Huda; Fitri Yani; Wedra Aprison (Prodi PAI STIT Sunan Giri Bima, 2025)
This study aims to (1) analyse the gap between the traditional PAI curriculum and the demands of Society 5.0, (2) identify the main challenges in implementing PAI digitalisation in schools, and (3) construct a Holistic PAI Curriculum Model (PAI-H) as a new theoretical framework that ensures the relevance of PAI in the digital age. This study adopts a Systematic Literature Review (SLR) approach involving qualitative content analysis of reputable international and national literature focusing on PAI curriculum reform, Society 5.0, teacher competencies, and digital ethics to produce credible data synthesis. The findings indicate that technology integration is often superficial, functioning only as a tool for delivering material, and that there is an urgent need to improve the competence of PAI teachers as Spiritual Mentors and shift the focus of the curriculum to be transdisciplinary. The PAI-H model is proposed as a solution that integrates technology, 4C skills, and digital ethics in utilising digital technology within a coherent framework, ensuring that PAI functions as a bastion of moderation. The presented PAI-H model offers strategic policy guidance for curriculum developers and educational institutions to produce graduates who are not only intellectually and digitally superior but also possess moral integrity and play an active role in positive social transformation.